ChatGPT as a Pedagogical Mediator in Foreign Language Learning: A Vygotskian and Interactionist Perspective from Nangarhar University: ChatGPT sebagai Mediator Pedagogis dalam Pembelajaran Bahasa Asing: Perspektif Vygotsky dan Interaksionis dari Universitas Nangarhar - Said Ikram Nael; Irfan Akhtar (SiRad: Pelita Wawasan, 2026)
Artificial Intelligence (AI) has changed from a simple subordinate device to a pedagogical mediator in the language learning process. In resource-poor environments such as Afghanistan, higher education institutions face the challenges of instructor shortages, limited language practice, and a lack of educational resources. This study evaluated the role of ChatGPT as a pedagogical mediator for German language students at Nangarhar University. Data were collected from 90 students through a questionnaire, which involved usage patterns, adaptive feedback, reduced learning concern, and learner autonomy. The results presented that ChatGPT supports language practice, instant and adaptive feedback, a low-anxiety situation, and learner autonomy. These findings are consistent with Vygotsky’s Zone of Proximal Development (ZPD), Communicative Language Teaching (CLT), and the Input–Interaction–Output model, and support the role of ChatGPT as a helper, not a substitute for the instructor. The study recommends that integrating ChatGPT into the language curriculum can develop learning consequences, and instructors properly integrate AI tools into the curriculum, certifying that they are consistent with instructor guidelines, ethics, and curriculum. [Kecerdasan Buatan (Artificial Intelligence/AI) telah berkembang dari sekadar perangkat pendukung sederhana menjadi mediator pedagogis dalam proses pembelajaran bahasa. Di lingkungan dengan sumber daya terbatas seperti Afghanistan, institusi pendidikan tinggi menghadapi berbagai tantangan, termasuk keterbatasan jumlah pengajar, minimnya kesempatan praktik berbahasa, dan kurangnya sumber daya pendidikan. Penelitian ini mengevaluasi peran ChatGPT sebagai mediator pedagogis bagi mahasiswa bahasa Jerman di Universitas Nangarhar. Data dikumpulkan dari 90 mahasiswa melalui kuesioner yang mencakup pola penggunaan, umpan balik adaptif, pengurangan kecemasan belajar, dan kemandirian belajar. Hasil penelitian menunjukkan bahwa ChatGPT mendukung praktik berbahasa, memberikan umpan balik yang cepat dan adaptif, menciptakan situasi belajar dengan tingkat kecemasan yang lebih rendah, serta meningkatkan kemandirian peserta didik. Temuan ini sejalan dengan konsep Zone of Proximal Development (ZPD) dari Vygotsky, Communicative Language Teaching (CLT), serta model Input–Interaction–Output, dan mendukung peran ChatGPT sebagai pendamping pembelajaran, bukan sebagai pengganti pengajar. Penelitian ini merekomendasikan integrasi ChatGPT ke dalam kurikulum pembelajaran bahasa untuk meningkatkan hasil belajar. Selain itu, para pengajar perlu mengintegrasikan perangkat AI secara tepat ke dalam kurikulum dengan memastikan kesesuaiannya terhadap pedoman pengajaran, etika, dan tujuan kurikulum.]